Through silicon vias: from a physical point of view to a compact models initiation. Issue 4 (1st July 2014) - Sun, Fengyuan; Lorival, Jean-Etienne; Calmon, Francis; Gontrand, Christian
Abstract : Purpose: – The substrate coupling and loss in integrated circuits are analyzed. Then, the authors extract impedances between any numbers of embedded contacts. The paper aims to discuss these issues. Design/methodology/approach: – The paper proposes a new substrate network 3D extraction technique, adapted from a transmission line method or Green kernels, but in the whole volume. Findings: – Extracting impedances between any numbers of embedded contacts with variable shapes or/and through silicon via. This 3D method is much faster comparing with FEM Originality/value: – Previous works consider TSVs alone, contacts onto the substrate. The authors do study entanglement between the substrate and the interconnections.